2008
DOI: 10.1037/0096-1523.34.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a moving distractor object on time-to-contact judgments.

Abstract: The effects of moving task-irrelevant objects on time-to-contact (TTC) judgments were examined in 5 experiments. Observers viewed a directly approaching target in the presence of a distractor object moving in parallel with the target. In Experiments 1 to 4, observers decided whether the target would have collided with them earlier or later than a standard (absolute identification task). A contrast effect was observed: If the distractor arrived later than the target, it caused a bias toward early responses, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
35
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 61 publications
(95 reference statements)
17
35
1
Order By: Relevance
“…This finding is consistent with previous studies (e.g., Oberfeld & Hecht, 2008;Petzoldt, 2014), and can be attributed to either a size-arrival effect (DeLucia, 1991) or a distance bias (Law et al, 1993), because the slower speed condition had a larger final optical vehicle size and a closer final distance than did the faster condition. A significant interaction between TTC level and speed, F(2, 80) = 27.397,ε = 1.000, p < .001, η p 2 = .407, indicated larger differences in TTC estimates between the two speeds with increasing actual TTC (see Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with previous studies (e.g., Oberfeld & Hecht, 2008;Petzoldt, 2014), and can be attributed to either a size-arrival effect (DeLucia, 1991) or a distance bias (Law et al, 1993), because the slower speed condition had a larger final optical vehicle size and a closer final distance than did the faster condition. A significant interaction between TTC level and speed, F(2, 80) = 27.397,ε = 1.000, p < .001, η p 2 = .407, indicated larger differences in TTC estimates between the two speeds with increasing actual TTC (see Fig.…”
Section: Resultssupporting
confidence: 92%
“…We also observed a significant effect of vehicle speed on TTC estimates, indicating that estimates were shorter when vehicle speed was slower. This finding is consistent with previous studies (e.g., Oberfeld & Hecht, 2008;Petzoldt, 2014) and can be attributed to a size-arrival effect (DeLucia, 1991) or to a distance bias (Law et al, 1993). Specifically, at slower speeds, when the screen goes blank, the final optical vehicle size is larger, and the vehicle is closer in terms of final distance, than in the faster condition.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The observer is required to make a simple response (e.g., press a button) at the time the object would have reached the target, had it continued along its trajectory. Using the PM task (see Lugtigheid & Welchman 2011), it is generally found that participants overestimate shorter TTC and underestimate longer TTC, with the transition point occurring at approximately 1000 ms (e.g., Manser & Hancock 1996;Schiff & Detwiler 1979;Oberfeld & Hecht 2008). Overt pursuit of the moving object is the default response in the PM task (Rosenbaum 1975) and is important for achieving accurate TTC estimation, with greater error exhibited if participants are instructed to fixate on a static location compared to when permitted to freely move their eyes (Bennett, Baurès, Hecht & Benguigui 2010;Makin & Poliakoff 2011;Peterken et al 1991).…”
Section: Introductionmentioning
confidence: 99%